Analysis Of The Influence Of Dividend Payout Ratio, Investment Opportunity Set And Return On Asset On The Value Of Manufacturing Companies - Nenden Hendayani; Adi Mursalin; Loso Judijanto; Ngurah Pandji Mertha Agung Durya; Naiyun Untung Utama (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to ascertain how a company's value is affected by factors such as leverage, return on assets, investment opportunity set, and dividend payout ratio. Associative research is what this study is. This study employed secondary data for its data collection. Annual financial reports and corporate annual reports that are released annually serve as secondary data for this study. Purposive sampling is the sample research technique employed. All manufacturing firms that are listed on the Indonesia Stock Exchange (BEI) serve as the research sample. Purposive sampling was used to choose the research sample. A literature review was the method of data collecting employed in this investigation. A multiple regression equation model is used in this study's hypothesis testing. The following conclusions can be made in light of the data that has been gathered and the outcomes of tests that have been conducted using the regression model: The value of a corporation is impacted by leverage. The value of the corporation is unaffected by ROA. IOS affects the value of a company. The dividend payout ratio affects the worth of the business.